Protection against internal hazards in the design of nuclear power plants : specific safety guide. (Safety standards series ;, 2021)
"Internal hazards have to be considered in the design of items important to safety in a nuclear power plant. The objective is to provide appropriate features to prevent internal hazards and mitigate their effects to ensure that safety is not compromised. This Safety Guide provides recommendations to regulatory bodies, nuclear power plant designers and licensees on hazard assessment (including for combinations of hazards) and design concepts for protection against internal hazards in nuclear power plants, in order to meet the requirements established in IAEA Safety Standards Series No. SSR 2/1 (Rev. 1), Safety of Nuclear Power Plants: Design. The following internal hazards are reviewed in this Safety Guide: fires, explosions, missiles, pipe breaks, flooding, collapse of structures and falling objects with a focus on heavy load drop, electromagnetic interference and release of hazardous substances originating from within the site boundary."--Publisher's description.